"Mulher no volante, perigo constante!?” a jornada de mulheres em um emprego dominado por homens através do espelho dos estereótipos de gênero - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The objective of this study was to identify the main challenges faced by female passenger transport drivers in Santana do Livramento/RS, with the analysis of gender stereotypes present in their work environment. The research, of a qualitative and exploratory nature, used thematic oral history as a methodology, with data collection through in-depth interviews. In total, 23 women who work as drivers for different transport services were interviewed, including taxi drivers and drivers for the Garupa, Tibbor and Rota77 apps. The research revealed that passenger transport drivers in Santana do Livramento have varied profiles, choosing the profession for reasons such as flexible working hours and the search for financial independence. However, they face challenges such as distrust of their competence, bullying and pressure to balance work and family responsibilities. Despite these difficulties, they show a great capacity for adaptation, adopting strategies to face prejudices and, in some cases, standing out positively among passengers. The research also highlighted the urgent need for a more inclusive and equal working environment, where gender is not seen as an obstacle, but as a characteristic that enriches diversity and strengthens the passenger transport sector.
“Woman drivers, constant danger!?” women’s journey in a male-dominated job through the looking glass of gender stereotypes
Keywords: Mulheres motoristas; Transporte de passageiros; Estereótipos; Desafios; Women drivers; Passenger transport; Stereotypes; Challenges; CIENCIAS SOCIAIS APLICADAS